2005
DOI: 10.1371/journal.pmed.0020179
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Psychosocial Needs in the Aftermath of the Tsunami

Abstract: MSF discusses its response to tackling mental health problems in Aceh, Indonesia, and explores some of the main concerns in responding effectively to mental health problems in an emergency setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 10 publications
2
7
0
Order By: Relevance
“…Prior to preparing the Indonesian translation, an English version was edited to a Flesch-Kincaid reading level of Grade 6. Psychiatric terms were avoided because psychiatric disorders may be culturally associated with shame ( de Jong, Prosser, & Ford, 2005). Written words were restricted to no more than two syllables and verified by bilingual therapists at the SHP.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior to preparing the Indonesian translation, an English version was edited to a Flesch-Kincaid reading level of Grade 6. Psychiatric terms were avoided because psychiatric disorders may be culturally associated with shame ( de Jong, Prosser, & Ford, 2005). Written words were restricted to no more than two syllables and verified by bilingual therapists at the SHP.…”
Section: Methodsmentioning
confidence: 99%
“…The prominence of religion in the lived experiences of the people participating in the study was suggested by Statements 68, 72, 83 and 86, all of which make reference to Allah/God and/or religion. The Muslim religion is central to Indonesian culture and traditions, in part intermingled with more traditional old Javanese beliefs in superstition and magic (de Jong et al, 2005). Religious influences denote the meaning individuals associate with their situation.…”
Section: Independent Statements On Sadness and Religionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Aceh, people traditionally consult local religious leaders, village leaders and dukuns, and rely on family support to deal with mental health problems. Some have questioned the validity, and highlighted the difficulties, of applying Western approaches in the context of significant cultural differences 9 , 10 . Potential barriers include competitiveness between traditional and Western services, the privileged nature of local spiritual knowledge and the perceived threat of competing cultural orientations.…”
Section: Discussionmentioning
confidence: 99%
“…Sri Lanka, a nation already in distress from periodic civil wars, experienced a devastating disaster on 26 December 2004, when an underground earthquake in the Indian Ocean measuring 9.2 on the Richter scale produced an immense tsunami (de Jong, 2005). This tsunami struck Sri Lanka and 13 other countries in and around the Indian Ocean.…”
mentioning
confidence: 99%